Fish abundance and distribution patterns related to environmental factors in a choked temperate coastal lagoon (Argentina) - Bruno, Daniel Osvaldo (2013)
The aim of this study was to assess the influence of environmental factors on the fish distribution and abundance in Mar Chiquita coastal lagoon. Seasonal fish sampling stations were distributed along the lagoon and grouped in three zones from a mixo-oligohaline waters zone with high contribution of freshwater to a mixo-eurihaline waters zone with high marine water influence. A mixo-mesohaline waters zone characterized the middle part of the lagoon. The results showed that the fish composition was dominated by marine estuarine dependent (ED) species in all three zones and in all seasons: Odontesthes argentinensis, Brevoortia aurea, Mugil liza and Micropogonias furnieri were the most representative species. The following important ecological category was freshwater fishes (FW), with Platanichthys platana and Jenynsia multidentata being the most representative species. According to the best model selected, by fitting generalized linear models, abundance of ED increased as water temperature increased during summer and autumn in all three zones. The highest abundance was recorded in the mixo-eurihaline waters zone. On the other hand, FW abundance increased with high rainfall and also when easterly winds blew. In conclusion, a differential habitat use by the species that occur in the Mar Chiquita coastal lagoon was observed. A few ED species dominated the fish composition but FW species also made use of the lagoon during periods of heavy rainfall.